2019
DOI: 10.1016/j.ydbio.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt inhibitor Dkk1 is required for maintaining the normal cardiac differentiation program in Xenopus laevis

Abstract: Wnt proteins can activate different intracellular signaling pathways. These pathways need to be tightly regulated for proper cardiogenesis. The canonical Wnt/β-catenin inhibitor Dkk1 has been shown to be sufficient to trigger cardiogenesis in gain-of-function experiments performed in multiple model systems. Loss-of-function studies however did not reveal any fundamental function for Dkk1 during cardiogenesis. Using Xenopus laevis as a model we here show for the first time that Dkk1 is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…Jag1 is expressed anteriorly, complementary to the region where the cardiac crescent resides [ 47 ]. Dkk1 , a Wnt modulator controlling cardiac differentiation [ 48 , 49 ], was also enriched in clusters 2 and 3. Id 2 , a gene essential for the specification of the heart tube-forming progenitors [ 50 ] is also enriched in clusters 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Jag1 is expressed anteriorly, complementary to the region where the cardiac crescent resides [ 47 ]. Dkk1 , a Wnt modulator controlling cardiac differentiation [ 48 , 49 ], was also enriched in clusters 2 and 3. Id 2 , a gene essential for the specification of the heart tube-forming progenitors [ 50 ] is also enriched in clusters 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate how Tet1/Tet2 regulate Wnt/β-catenin signaling, we examined the level of DKK-1, an upstream inhibitor of the WNT pathway 27 , and found that DKK-1 was downregulated in Tet1/Tet2 siRNA-treated PDLSCs. Immunofluorescence staining showed co-localization of DKK-1 with MSC surface marker CD146 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Jag1 is expressed anteriorly, complementary to the region where the cardiac crescent resides (Przemeck et al, 2003). Dkk1, a Wnt modulator controlling cardiac differentiation (David et al, 2008;Guo et al, 2019;Phillips et al, 2011), is also uniquely enriched in the right ventricle cluster. Id1 and 2, which are essential for the specification of the heart tube-forming progenitors (Cunningham et al, 2017) are enriched in both the left and right ventricle clusters but absent in the outflow and atrial clusters.…”
Section: Genetic Tracing Of Primitive Streak Cells Using a Tamoxifen mentioning
confidence: 99%